The cingulate cortex of older adults with excellent memory capacity. (January 2017) - Lin, Feng; Ren, Ping; Mapstone, Mark; Meyers, Steven P.; Porsteinsson, Anton; Baran, Timothy M.; ,
Abstract: Memory deterioration is the earliest and most devastating cognitive deficit in normal aging and Alzheimer's disease (AD). Some older adults, known as "Supernormals", maintain excellent memory. This study examined relationships between cerebral amyloid deposition and functional connectivity (FC) within the cingulate cortex (CC) and between CC and other regions involved in memory maintenance between Supernormals, healthy controls (HC), and those at risk for AD (amnestic mild cognitive impairment [MCI]). Supernormals had significantly stronger FC between anterior CC and R-hippocampus, middle CC (MCC) and L-superior temporal gyrus, and posterior CC (PCC) and R-precuneus, while weaker FC between MCC and R-middle frontal gyrus and MCC and R-thalamus than other groups. All of these FC were significantly related to memory and global cognition in all participants. Supernormals had less amyloid deposition than other groups. Relationships between global cognition and FC were stronger among amyloid positive participants. Relationships between memory and FC remained regardless of amyloid level. This revealed how CC-related neural function participates in cognitive maintenance in the presence of amyloid deposition, potentially explaining excellent cognitive function among Supernormals.